Politics, Philosophy, Terror : Essays on the Thought of Hannah Arendt. - Villa, Dana (Princeton University Press, 2001)
Hannah Arendt's rich and varied political thought is more influential today than ever before, due in part to the collapse of communism and the need for ideas that move beyond the old ideologies of the Cold War. As Dana Villa shows, however, Arendt's thought is often poorly understood, both because of its complexity and because her fame has made it easy for critics to write about what she is reputed to have said rather than what she actually wrote. Villa sets out to change that here, explaining clearly, carefully, and forcefully Arendt's major contributions to our understanding of politics, mod.